Relative Influence of Plant Quality and Natural Enemies on the Seasonal Dynamics of Bemisia tabaci (Hemiptera: Aleyrodidae) in Cotton. Issue 3 (9th September 2014) - Asiimwe, Peter; Naranjo, Steven E.; Ellsworth, Peter C.
Abstract : The abundance and distribution of insect herbivores is determined by, among other things, plant quality and natural enemies. These two factors vary temporally and spatially, subsequently affecting seasonal population dynamics. The relative influence of plant quality and natural enemies on the seasonal dynamics of Bemisia tabaci (Gennadius) was investigated in a 3-yr field study in cotton. Plant quality was manipulated through varying irrigation regimes: irrigations done at 20, 40, and 60% soil water depletions; and natural enemy densities were manipulated using broad spectrum insecticide applications that reduced their densities compared with unsprayed controls. In each year, densities of B. tabaci eggs, large nymphs and adults were consistently higher when natural enemy densities were reduced compared with when they were left unaltered, regardless of irrigation regime. In contrast, effects of plant quality on densities of all whitefly stages were weak and inconsistent. In addition, natural enemy densities and predator:prey ratios also were not generally affected by plant quality. Interactions between natural enemies and plant quality on whitefly dynamics were rare. In general, whitefly densities were elevated two-thirds of the time and increased two- to sixfold when natural enemy densities were reduced compared with plant quality effects which influenced whitefly densities about one-third of the time and were expressed inconsistently over the years. This indicates that natural enemies exert a comparatively greater influence on seasonal dynamics of B. tabaci in cotton than plant quality, as manipulated by differential irrigation.